Design of TS Fuzzy Systems Event triggered Transmission Scheme H ∞ Control - WANG Jie xun (Journal of Harbin University of Science and Technology)
To study the design of Hinfinity faulttolerant controller for a class of Nonlinear Networked Control Systems (NNCS) with actuator failures we use state feedback control strategy. First the nonlinear system is modeled as a TS fuzzy model, and then the sufficient condition for the existence of fault tolerant controller with Hinfinity performance is derived. Then under the contract transformation, the faulttolerant controller gains are calculated. Finally, a numerical example shows the feasibility of the proposed theory.